Bioactive Compounds in Grain Fermentation - Peng Wu; Ni Wang (Fermentation, 2024)
As we conclude our exploration of the Special Issue, “Bioactive Compounds in Grain Fermentation”, it is essential to revisit the origins of this initiative, providing a clear understanding of its objectives [...]